2020
DOI: 10.3390/ijerph17165985
|View full text |Cite
|
Sign up to set email alerts
|

Cycle of Perpetual Vulnerability for Women Facing Homelessness near an Urban Library in a Major U.S. Metropolitan Area

Abstract: Background: Homelessness among women and the multiple vulnerabilities they endure (sexual exploitation/human trafficking, violence, and mental health issues) is a perpetually unresolved issue in the U.S. and globally. Methods: This study is based on qualitative in-depth interviews accompanied by brief socio-demographic surveys conducted among 32 total participants, consisting of cisgender females (n = 17) and cisgender males (n = 15) experiencing homelessness at a large public library. Results: Of the women, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(36 reference statements)
2
4
0
Order By: Relevance
“…Previous research on the Mass and Cass encampment found that women reported high rates of survival sex and sexual assaults [ 39 , 40 ]. Consistent with literature on homeless individuals’ experiences of safety, participants in this study felt safer in this shelter than in encampments or other local shelters, reporting freedom from coercion and less interpersonal conflict when their basic material needs were met [ 38 , 41 ]. This safety was cultivated by the gender-specific setting, the staff’s ability to support women with complex mental health and trauma histories, and the low-conflict, nurturing environment [ 11 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 77%
“…Previous research on the Mass and Cass encampment found that women reported high rates of survival sex and sexual assaults [ 39 , 40 ]. Consistent with literature on homeless individuals’ experiences of safety, participants in this study felt safer in this shelter than in encampments or other local shelters, reporting freedom from coercion and less interpersonal conflict when their basic material needs were met [ 38 , 41 ]. This safety was cultivated by the gender-specific setting, the staff’s ability to support women with complex mental health and trauma histories, and the low-conflict, nurturing environment [ 11 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 77%
“…Library patrons who face mental health crises, violence, human trafficking, and sexual assault on the street need more targeted interventions [ 28 ]. For example, studies show that those who are unstably housed and use opioids, fentanyl, and methamphetamines, benefit from “housing first” models for recovery [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social workers, alongside community partners with lived experiences of homelessness, respond to the needs of people experiencing homelessness via outreach and crisis intervention in spaces where others may not go (e.g., street outreach, public libraries) [ 37 , 38 , 39 ], or in alternative approaches to ones that have not been successful for preventing or effectively mitigating homelessness or its associated harms. For example, police-led Homeless Outreach Teams have become a common feature in city police departments across the US.…”
Section: An Interdisciplinary Academic-practice Partnership Modelmentioning
confidence: 99%